STRATEGIES FOR SUPPORTING STUDENTS WITH ALEXITHYMIA AND DEPRESSION (Psychology Travelogs, 2025)
The article is devoted to the problem of overcoming alexithymia and depression in students. Based on the review of scientific literature, it was found that alexithymia and depressive manifestations are quite common among students in adolescence, there is a direct correlation between alexithymia and depression, and they are a factor in the occurrence of psychosomatic diseases, other mental disorders, personal and academic difficulties. The purpose of the article is to review possible ways of psychological support for students with alexithymia and depression. The following conclusions were made based on the results of the review. For the timely detection of alexithymia and depressive manifestations in students, it is necessary to conduct preventive examinations in order to further organize appropriate psychological educational and developmental activities in educational institutions. Psychological support for students with alexithymia and depression can be provided using a comprehensive approach that includes psychological counseling, art-therapy, training in self-regulation and stress management methods, educational activities aimed at developing emotional intelligence and skills for constructive social interaction, and creating a supportive social environment. It is important to create conditions in which students feel supported and understood. One way to implement this task may be to create special support groups for students in which they could safely share their experiences and improve their understanding of their own emotions and needs. To overcome social isolation and feelings of loneliness, it is also necessary to provide students with the opportunity to participate in various activities that promote social integration, such as interest clubs, volunteer projects, and social initiatives. It is important to take into account the individual characteristics and needs of each student and create conditions in which they can feel safe and comfortable in order to develop their personal and professional competencies.
Keywords: alexithymia; depression; students; psychological assistance; psychological support; mental health; emotional intelligence